Arthroscopic Treatment of Horizontal Acromioclavicular Joint Instability With Reverse Weaver-Dunn Procedure - Oleg Milenin, M.D.; Andrey Ratiev, M.D., F.D.; Karen Egiazaryan, M.D., F.D. (Arthroscopy Techniques)
Acromioclavicular (AC) joint instability is a common issue. The stability of this joint depends on the combined support of the coracoclavicular ligaments and the AC ligament and capsular structures. Several surgical methods for treating horizontal instability have been reported. The arthroscopic Weaver-Dunn procedure, involving the transfer of the acromial end of the acromial-coracoid ligament to the clavicle, is a well-known option for coracoacromial reconstruction, particularly for addressing vertical instability. This technique has demonstrated positive functional and clinical outcomes. We modified the Weaver-Dunn procedure to treat horizontal instability of the AC joint. Using this technique, we transferred the coracoid end of the coracoacromial ligament to the clavicle.